Utilizing Linkedin for Personal Branding and Workforce Preparation for Office Administration Students at SMK Airlangga - Alamsyah, Andi Indra Saputra; Kende, Yizreel Junus; Prabawani, Isti; Astuti, Yuni (Sekolah Tinggi Ilmu Hukum Awang Long, 2025)
In today's era of globalization and advancing digitalization, the job market is increasingly competitive, demanding that job seekers master not only technical skills but also comprehensive soft skills. This is especially true for Vocational High School (SMK) students, particularly those in the Office Management Automation (OTKP) program at SMK Airlangga, who face the challenge of preparing themselves for a competitive work environment. LinkedIn, as a global professional networking platform, serves as a vital tool for building personal branding and expanding professional networks for OTKP students. However, effectively using LinkedIn requires a deep understanding of profile creation, personal branding principles, and networking strategies. The community service program, titled “Utilizing LinkedIn for Personal Branding and Workforce Preparation for OTKP Students at SMK Airlangga,” aims to provide training and insights to students on how to maximize LinkedIn for their professional advantage. This program will cover creating an outstanding LinkedIn profile, strategies for building and maintaining professional networks, and effective communication techniques on the platform. Additionally, it seeks to enhance students' awareness and understanding of the importance of personal branding in today’s workforce. The goal of this initiative is to equip students with the tools and strategies needed to succeed in utilizing LinkedIn and other online resources, helping them build confidence in presenting themselves and their skills to the world. It will also introduce them to essential professional skills, such as communication and networking. It is hoped that this effort will open up broader opportunities for students to enter the competitive job market with strong preparation.